MANAJEMEN HUBUNGAN MASYARAKAT (HUMAS) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI MTs AL-AMIRIYYAH BLOKAGUNG BANYUWANGI - Amirotun Nahdliyah; Aliyah Uhwatun Hasanah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Public relations management in increasing community participation is one method to foster and develop a harmonious inter-community relationship between the madrasa and the community. Due to the success of an educational institution in achieving a mission and goals that have been set. The focus of the research: 1) How is the management of public relations at MtsABlokagung Banyuwangi?,2) How is the participation of the community around MtsABlokagung Banyuwangi?, 3) What is the role of public relations management in increasing community participation at MTs A Blokagung Banyuwangi?. The purpose of the study was to analyze the public relations management of MTs A Blokagung Banyuwangi, to determine the community participation of MTs A Blokagung Banyuwangi, and to determine the management of public relations in increasing community participation at MTs A Blokagung Banyuwangi. Descriptive qualitative research method using observation, interviews, and documentation as data collection techniques. Sources of data in this study include, 1) person (people), namely, (a) the head of the madrasa, (b) waka public relations. 2) place (place), namely, at MTs Al-Amiriyyah Blokagung Banyuwangi. The results obtained are as follows: Public relations management at MTs Al-Amiriyyah Blokagung Banyuwangi using POAC, namely: Planning, Organizing, Actuating, and Controlling.